SNORA13 antisense oligonucleotides enhances the therapeutical effects of 5-fluorouracil in colon adenocarcinoma - Wang, Yanzhi; An, Huihui; Zhang, Yaou; Lyu, Qing Rex; Zhang, Zhe (Frontiers in Pharmacology, 2025)
IndroductionColorectal cancer (CRC) is a prevalent malignancy and is the second leading cause of cancer-related mortality worldwide. 5-Fluorouracil (5-FU) is widely used in clinical intervention, however, drug resistance to 5-FU poses a significant challenge to treatment efficacy. Small nucleolar RNAs (snoRNAs) are a class of nuclear non-coding RNAs that mainly play roles in post-transcriptional RNA processing and modification in ribosomal RNA, which is crucial for sustaining protein synthesis. This study aimed to identify differentially expressed snoRNAs in CRC and pinpoint a specific snoRNA that may exert a synergistic effect with 5-FU administration.MethodsCombinatorial small RNA array of clinical samples and data analysis from The Cancer Genome Atlas (TCGA) database were used to identify the differentially expressed snoRNAs in colorectal cancer (CRC). To investigate the role of SNORA13 in CRC, loss-of-function (LoF) study was conducted using transient antisense oligonucleotides (ASOs) transfection and SNORA13 knockout with CRISPR-Cas9 genome editing in HT29 colon adenocarcinoma cell line. A combined administration of SNORA13-ASO and 5-Fluorouracil (5-FU) was performed in nude mice xenograft model to verify the synergistic inhibitory effect. RNA-seq, Ribo-seq and proteomics were performed to identify the downstream target of SNORA13, and qRT-PCR and Western Blot were used to confirm the results of multi-omics analysis.ResultsThe analysis of small RNA array data combined with the snoRNA expression profile in TCGA database determined that SNORA13 is commonly increased in CRC tissues. The LoF study revealed that the cell proliferation and colony formation are significantly suppressed upon SNORA13 deficiency. Next, the xenografted tumor model in nude mice demonstrated that the smaller tumorigenesis in SNORA13 knockout HT29 cell lines, and SNORA13 ASO enhances the anti-cancer efficacy of 5-FU. Finally, multi-omics analysis and molecular experimental validation revealed that nicotinamide N-methyltransferase (NNMT) is significantly suppressed in SNORA13 knockout HT29 cell lines.ConclusionOur study revealed SNORA13 is highly expressed in CRC and demonstrated knockdown of SNORA13, especially combined with 5-FU administration, may represent a promising therapeutic approach for CRC treatment.